Pengembangan Kurikulum Pendidikan Agama Islam - Ubaidillah (STAI Ihyaul Ulum Gresik, 2024)
The purpose of this study is to identify the Islamic Education (PAI) curriculum development model at SMK Ihyaul Ulum Dukun Gresik. This research employs a qualitative method with a descriptive approach. Data were collected through interviews, observations, and document reviews. The data sources included M. Miftah Wahyudi, the Vice Principal of Curriculum, and the SMK Ihyaul Ulum Dukun Gresik Curriculum Documents for the 2023/2024 Academic Year. The findings indicate that the curriculum development model is implemented through four stages: first, determining the objectives of Islamic Education; second, designing learning experiences; third, organizing material into subjects; and fourth, conducting annual curriculum evaluations to measure the effectiveness of student achievement and knowledge absorption. This model bears a resemblance to Tyler’s curriculum development theory.